Extraction and characterization of β-fructofuranosidases produced by Kluyveromyces marxianus CCMB 322 - Peixoto, Albert Souza (2020)
Invertase (β-fructofuranosidase, EC 3.2.1.26) catalyzes sucrose hydrolysis into glucose and fructose and it is one of the simplest carbohydrases. These enzymes occur widely in nature and their presence has been reported in microorganisms and plants. Since yeasts are the main industrial source, most researches concerning this enzyme have focused on invertase extracted from such source. This study extracted and characterized inverted intracellular (Inv-I) and extracellular (Inv-E) of Kluyveromyces marxianus CCMB 322 isolated in the baiano semi-arid region. Kluyveromyces marxianus CCMB 322 produces intracellular and extracellular invertase with different characteristics. The optimum activity was achieved at approximately pH 3.9 and 45ºC, in Inv-I and Inv-E. The invertases produced by K. marxianus CCMB 322 showed thermal stability similar to that found in other studies. The Km and Vmax values of the Inv-I enzyme were 61.12mM and 5.56 µmol/mL.min-1, but the Km and Vmax values of the Inv-E enzyme were 76.5mM and 0.364 µmol/mL.min-1. Inverted from K. marxianus is a higher affinity for sucrose compared to enzymes from other sources.